Effect of Hypothyroidism of Women in the First Trimester of Pregnancy in Al-Basra City (المجلة الدولية للبحوث العلمية, 2024)
Evaluating the thyroid gland's functioning in expectant women at Basra's Abi Al-Khasib Hospital, in order to better understand the physiological changes that women experience during pregnancy, especially those that affect the thyroid gland. Due to their significance in the healthy development of the embryonic brain. This study tried to concentrate on thyroid hormones, which depend on a steady supply of hypothyroidism; too little or too much of them can impair the fetus's neurological development. However, an imbalance in the thyroid gland increases the risk of complications during labor and delivery, including preterm birth, pre-eclampsia, and placental abruption.The purpose of the study was to determine if hypothyroidism during the first trimester of pregnancy affected the results of gland function tests or not.Two groups of 20 women were selected for the study: one group included 15 pregnant women with the afflicted condition, while the other group included 5 normal, non-pregnant women who were in the first trimester of their pregnancies. The hormones FT4, FT3, and TSH were all scrutinized.According to the study, there is a statistically significant difference between pregnant and non- pregnant women's levels of the two thyroid hormones, tri-thyronine, and thyroxin, when it comes to how well the thyroid operates during pregnancy.